GAYA BAHASA IRONI DAN SARKASME KIKY SAPUTRI PADA TAYANGAN LAPOR PAK - Nurvia, Riska; Usman, Usman; Fitri, Sakinah (Fakultas Bahasa dan Sastra Indoensia, 2025)
This research aims to describe the linguistic style of Kiky Saputri irony and sarcasm in the show “Lapor Pak”; describe the meaning of Kiky Saputri's language style of irony and sarcasm in the show